Two New Species and a Subspecies of Brachymeria Westwood (Hymenoptera: Chalcididae) in the Collections of Forest Research Institute, Dehra Dun - Jospph, K. J.; Narendran, T. C.; Joy, P. J. (Indian Forester, 1972)
Two new species and a subspecies of Brachymeria Westwood, viz., Brachymeria dunensis, Brachymeria calopeplae and Brachymeria hime atteviae are described. This paper contains descriptions of two new species and a subspecies of Brachymeria Westwood from the collections of Forest Research Institute, Dehra Dun. The type specimens will be deposited in the same institution.